Lumbar hemangiopericytoma - Calvelo, Agustín A.; Vivas, Eudoxio; Falconi, Luis; Castiglioni, Dinorah (Cirugía del Uruguay, 1978)
A case of malignant hemangiopericytoma of the lumbar somatic soft tissues is presented. It was treated by radical en bloc surgical excision. Now it is asyntomatic after 18 months. Long term follow-up is recommended because local recurrence or metastasis may occur longer than 5 years after apperently successful treatment.